Sistem Pendukung Keputusan Penentuan Penerima Beasiswa Daerah Menggunakan Metode MABAC: Studi Kasus Pemda Kabupaten Sikka - Jekonia Nelchika Titing; Tri Ana Setyarini (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
The selection process for regional scholarship recipients often involves multiple criteria and a large number of applicants. This situation can make it difficult for the local government to make objective and efficient decisions. This study aims to design a Decision Support System (DSS) to assist the local government, particularly in Sikka Regency, in the scholarship recipient selection process. The MABAC method was chosen as the calculation method in this Decision Support System because of its capability to handle multi-criteria problems and produce accurate results.The system is expected to select prospective scholarship recipients objectively, transparently, and efficiently. This research produces an information system that can assist the local government in decision-making regarding scholarship determination. By using this system, the selection process is expected to become faster, more accurate, and accountable. In addition, the system can provide recommendations to the local government regarding current scholarship policies